Baroque art and music (Clearvue/eav, 1986)
Following an on-camera by Roya Megnot, introduces the student to the art and music of the baroque period, 1600-1750. Traces the advent of the Baroque era through the painting of Caravaggio and Carracci and Rubens, sculpture by Bernini, and music of Corelli which represent the international style of the high Baroque. Also describes Baroque in Northern Europe.